THE EFFECT OF DIFFERENT DOSES OF PROBIOTICS IN COMMERCIAL FEEDINGS ON THE SURVIVAL AND LENGTH OF KOI FISH (Cyprinus rubrofuscus) SEEDS: PENGARUH PERBEDAAN DOSIS PROBIOTIK PADA PAKANvKOMERSIL TERHADAP KELANGSUNGAN HIDUP DAN PANJANG BENIH IKAN KOI (Cyprinus rubrofuscus) - Kurnia; Ori Marlinda; Nurhatijah; Indah Permata Sari; Ahmad supriatna (PT. ROCE WISDOM ACEH, 2024)
This study aims to determine the growth of Koi (Cyprinus rubrofuscus) with the addition of probiotics. This research was carried out in the wet laboratory of the study program for Teknologi Produksi Benih dan Pakan Ikan Politeknik Indonesia Venezuela, from March to April 2024. The method used was a laboratory experimental method and a nonfactorial completely randomized design (CRD) consisting of 4 treatments and of 4 replications viz. based, namely A (control), B (3 ml addition of probiotics), C (6 ml addition of probiotics), and D (9 ml addition of probiotics). Based on the results of observations in the field for an average survival value of 100%. The results showed that the use of probiotics for Koi fish hatchery media had no significant effect on the survival of Koi fish, so further tests were carried out to determine the best treatment for producing Koi fish length and weight growth, it was known that probiotics were the best treatment in this study.